2016
DOI: 10.1177/0013164416670983
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rating Unfamiliar Items on Angoff Passing Scores

Abstract: The Angoff standard setting method relies on content experts to review exam items and make judgments about the performance of the minimally proficient examinee. Unfortunately, at times content experts may have gaps in their understanding of specific exam content. These gaps are particularly likely to occur when the content domain is broad and/or highly technical, or when non-expert stakeholders are included in a standard setting panel (e.g., parents, administrators, or union representatives). When judges lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…More recently, Clauser and Hambleton () reported on a study in which judges were asked to provide Angoff judgments for all items but were asked to mark items for exclusion if the content material was so unfamiliar that they believed they could not make a reasonable judgment. They reported that, after accounting for judge stringency and perceived item difficulty, items marked as unfamiliar received judgments slightly over .10 lower than expected on a zero‐to‐one probability scale.…”
mentioning
confidence: 99%
“…More recently, Clauser and Hambleton () reported on a study in which judges were asked to provide Angoff judgments for all items but were asked to mark items for exclusion if the content material was so unfamiliar that they believed they could not make a reasonable judgment. They reported that, after accounting for judge stringency and perceived item difficulty, items marked as unfamiliar received judgments slightly over .10 lower than expected on a zero‐to‐one probability scale.…”
mentioning
confidence: 99%
“…Standard setting judges in their study involved practicing physicians as well as non-physician PhDs (e.g., Professors of Microbiology). Their results concluded that when the non-expert judges were asked to determine the cutoff score of an unfamiliar item, they provide lower passing score than for a familiar item (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is logical to assume that expert knowledge may influence perceptions of importance (Clauser et al, 2016), but Burr S, Martin T, Edwards J, Ferguson C, Gilbert K, Gray C, Hill A, Hosking J, Johnstone K, Kisielewska J, Milsom C, Moyes S, Rigby-Jones A, Robinson I, Toms N, Watson H, Zahra D MedEdPublish https://doi.org/10.15694/mep.2021.000032.1 there are several elements of importance that can be considered. Advocacy for the importance of each judge's own area of expertise in content knowledge may be moderated, to some extent by rating each question in more than one element of importance, for example, the links to other concepts, the frequency with which the concept is encountered, and the consequences of not understanding a concept (Neve et al, 2019).…”
Section: Acceptability Of Conceptualisation and The Need To Agree Weightingsmentioning
confidence: 99%